Impacts of some building passive design parameters on heating demand for a cold region - Aksoy, U. Teoman; Inalli, Mustafa (Pergamon-Elsevier Science Ltd, 2006)
In this study, the impact of passive design parameters such as building shape and orientation position on heating demand has been theoretically investigated. Therefore, a transient heat transfer problem in the building envelope with insulation and without insulation is solved by using the finite difference method. The considered buildings are placed on the ground with the azimuth angles from 0 degrees to 90 degrees. The heat loss per unit area of the buildings is computed by hour-hour and the yearly energy consumption of the buildings is also determined in the simulation model. The climatic data of Elazig (38.4 degrees N), a city located in a cold region of Turkey, are considered for the analysis. It is shown that buildings with a square shape have more advantages, and the most suitable orientation angles are 0 degrees and 80 degrees for buildings having shape factors (the ratio of building length to building depth) 2/1 and 1/2, respectively. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: building passive parameters; climatic comfort; heating demand; cold region